Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5334/jcr.174
|View full text |Cite
|
Sign up to set email alerts
|

Brain Microdialysate Monoamines in Relation to Circadian Rhythms, Sleep, and Sleep Deprivation – a Systematic Review, Network Meta-analysis, and New Primary Data

Abstract: Disruption of the monoaminergic system, e.g. by sleep deprivation (SD), seems to promote certain diseases. Assessment of monoamine levels over the circadian cycle, during different sleep stages and during SD is instrumental to understand the molecular dynamics during and after SD. To provide a complete overview of all available evidence, we performed a systematic review. A comprehensive search was performed for microdialysis and certain monoamines (dopamine, serotonin, noradrenaline, adrenaline), certain monoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 147 publications
1
28
0
1
Order By: Relevance
“…Shank3 ∆C mice were reported to have deficits in motor coordination (Kouser et al, 2013); however, under a 12:12 hr LD schedule their wheel-running activity increases over time (Supplementary file 1, Source data 1). Daily rhythms of activity in rodents are linked to circadian oscillations in dopamine release (Feenstra et al, 2000; Menon et al, 2019) in the frontal cortex as well as in the striatum, a motor region with high levels of Shank3 expression (Peça et al, 2011). Together with a reduction in circadian gene expression, this DD-specific activity deficit suggests that the mutant sleep phenotype involves clock gene functions outside of their central time-keeping role.…”
Section: Discussionmentioning
confidence: 99%
“…Shank3 ∆C mice were reported to have deficits in motor coordination (Kouser et al, 2013); however, under a 12:12 hr LD schedule their wheel-running activity increases over time (Supplementary file 1, Source data 1). Daily rhythms of activity in rodents are linked to circadian oscillations in dopamine release (Feenstra et al, 2000; Menon et al, 2019) in the frontal cortex as well as in the striatum, a motor region with high levels of Shank3 expression (Peça et al, 2011). Together with a reduction in circadian gene expression, this DD-specific activity deficit suggests that the mutant sleep phenotype involves clock gene functions outside of their central time-keeping role.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to corticosterone, activity of arousal system mediators is also influenced by circadian rhythm, with norepinephrine reaching its peak at the onset of the dark phase [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several elements of DA signaling have a diurnal rhythm, including expression of DA receptors and tyrosine hydroxylase (TH), the rate-limiting enzyme in DA synthesis (Castañeda et al, 2004;Weber et al, 2004;Ferris et al, 2014;Ozburn et al, 2015;Sidor et al, 2015). Numerous rodent studies have reported diurnal changes in extracellular DA levels in various brain regions such as the prefrontal cortex and nucleus accumbens, with generally higher levels at night when rodents are active (Smith et al, 1992;Hood et al, 2010;Menon et al, 2019). Similarly, circulating DA levels in men peak during the day (Sowers and Vlachakis, 1984).…”
Section: Influence Of the Circadian Clock And Sleep On Dopamine Signamentioning
confidence: 99%
“…There are also changes in extracellular DA levels across the spontaneous sleep/wake cycle. The fluctuations vary between brain regions, but generally levels are higher during wakefulness (Léna et al, 2005;Dong et al, 2019;Menon et al, 2019). In the mouse striatum, DA levels also exhibit dynamic changes within periods of wakefulness and at sleep/wake state transitions (Dong et al, 2019).…”
Section: Influence Of the Circadian Clock And Sleep On Dopamine Signamentioning
confidence: 99%